2020
DOI: 10.1038/s41467-020-17289-z
|View full text |Cite
|
Sign up to set email alerts
|

Gas hydrate dissociation linked to contemporary ocean warming in the southern hemisphere

Abstract: Ocean warming related to climate change has been proposed to cause the dissociation of gas hydrate deposits and methane leakage on the seafloor. This process occurs in places where the edge of the gas hydrate stability zone in sediments meets the overlying warmer oceans in upper slope settings. Here we present new evidence based on the analysis of a large multidisciplinary and multi-scale dataset from such a location in the western South Atlantic, which records massive gas release to the ocean. The results pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 67 publications
2
58
1
Order By: Relevance
“…When it exists, the BSR often decreases as the seabed shallows until it intersects with the seabed, where it is known as the landward limit of gas hydrate stability zone (LLGHSZ) representing the shallowest water depth of GHSZ. Due to limited methane supply and the anaerobic oxidation of methane (AOM) at shallow depth, both BSR and LLGHSZ are rarely visible in the vicinity of the theoretical LLGHSZ in seismic data in many gas hydrate occurrence areas [4,35,[48][49][50]. In areas without BSR development, it is difficult to recognize the GHSZ which may hinder judging whether the methane source for the seabed methane seepage is related with the gas hydrate systems or not.…”
Section: Gas Hydrate Stability Zone (Ghsz)mentioning
confidence: 99%
See 3 more Smart Citations
“…When it exists, the BSR often decreases as the seabed shallows until it intersects with the seabed, where it is known as the landward limit of gas hydrate stability zone (LLGHSZ) representing the shallowest water depth of GHSZ. Due to limited methane supply and the anaerobic oxidation of methane (AOM) at shallow depth, both BSR and LLGHSZ are rarely visible in the vicinity of the theoretical LLGHSZ in seismic data in many gas hydrate occurrence areas [4,35,[48][49][50]. In areas without BSR development, it is difficult to recognize the GHSZ which may hinder judging whether the methane source for the seabed methane seepage is related with the gas hydrate systems or not.…”
Section: Gas Hydrate Stability Zone (Ghsz)mentioning
confidence: 99%
“…Seabed methane seepage is often characterized by seabed manifestations such as methane flares, pockmarks, carbonate crusts on mounds or pavements, coral reefs, mud volcanoes, hydrate pingoes, and chemosynthetic biological communities [1,4,12,52,53]. The size and density of these seabed manifestations reflect the volume of methane transferred from geosphere to hydrosphere or even the atmosphere, whose presence also indicates the existence of underlying hydrocarbon reservoirs or gas hydrate systems [1,53].…”
Section: Characterization Of Seabed Methane Seepage Manifestationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Naturally occurring methane hydrate is abundant in oceanic settings, but changes in pressure and temperature (P-T) cause it to dissociate, potentially allowing methane to escape to the atmosphere and amplify climatic change (Ruppel and Kessler, 2017) or oxidize in seawater and contribute to ocean acidification (Biastoch et al, 2011). Seaward shifts of the updip feather edge of marine methane hydrate resulting in methane venting to the ocean have been documented due to contemporary warming of bottom waters (Skarke et al, 2014;Ketzer et al, 2020), but this has not been demonstrated for past climate change on canyon-incised margins. There are >5800 submarine canyons, with a total length of 254,000 km, on Earth (Harris and Whiteway, 2011), and methane emissions and hydrate have been detected in canyons (e.g., Barkley Canyon, offshore British Columbia, Canada: Thomsen et al, 2012; Hudson Canyon, offshore northeastern United States: Weinstein et al, 2016).…”
Section: Introductionmentioning
confidence: 99%